Theory of the Trojan-Horse Method − From the Original Idea to Actual Applications - Typel Stefan (EPJ Web of Conferences, 2017)
The origin and the main features of the Trojan-horse (TH) method are delineated starting with the original idea of Gerhard Baur. Basic theoretical considerations, general experimental conditions and possible problems are discussed. Significant steps in experimental studies towards the implementation of the TH method and the development of the theoretical description are presented. This lead to the successful application of the TH approach by Claudio Spitaleri and his group to determine low-energy cross section that are relevant for astrophysics. An outlook with possible developments in the future are given.